2017
DOI: 10.1093/jee/tox027
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Trends in Insecticide Resistance of Field Populations of Sogatella furcifera (Hemiptera: Delphacidae) in Guizhou Province, China, 2012–2015

Abstract: Sogatella furcifera (Horváth) is a migratory insect that is one of the most important pest species on rice in many Asian countries. Control of S. furcifera (Hemiptera: Delphacidae) primarily depends on the use of chemical insecticides, and with this extensive reliance on pesticides, determining the degree of resistance of S. furcifera populations to the chemicals used for its control is essential. In this study, the resistance level to six conventional insecticides in five populations of S. furcifera from Guiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…This shows that the Nagapattinam population has developed highest resistant level (6.2 fold) followed by Bhavani (4.1 fold), Coimbatore (2.8 fold) and the population from this region had been frequently sprayed by the imidacloprid 17.8% SL. The results of our study is on par with [18] S. furcifera from five regions of Guizhou province recorded low resistance against thiamethoxam (RR = 0.27 -9.69) and susceptibility to moderate resistance against imidacloprid (RR = 0.71 -26.06) The imidacloprid resistant strains of WBPH were obtained through laboratory selections for cross resistance profiling showed resistance fold of 10.4 [19] . The population from Yunnan, Jiangsu and Zhejiang provinces resulted in moderate resistance to the imidacloprid with LC50 value ranging from 0.2 ppm to 1.091 ppm.…”
Section: Resultssupporting
confidence: 53%
“…This shows that the Nagapattinam population has developed highest resistant level (6.2 fold) followed by Bhavani (4.1 fold), Coimbatore (2.8 fold) and the population from this region had been frequently sprayed by the imidacloprid 17.8% SL. The results of our study is on par with [18] S. furcifera from five regions of Guizhou province recorded low resistance against thiamethoxam (RR = 0.27 -9.69) and susceptibility to moderate resistance against imidacloprid (RR = 0.71 -26.06) The imidacloprid resistant strains of WBPH were obtained through laboratory selections for cross resistance profiling showed resistance fold of 10.4 [19] . The population from Yunnan, Jiangsu and Zhejiang provinces resulted in moderate resistance to the imidacloprid with LC50 value ranging from 0.2 ppm to 1.091 ppm.…”
Section: Resultssupporting
confidence: 53%
“…12) In Asia, resistance against several types of insecticides has been reported in BPH and WBPH. [13][14][15][16] Matsumura et al reported that BPH has a decreased susceptibility to imidacloprid and thiamethoxam, while WBPH remains susceptible to imidacloprid but not to fipronil in the Red River Delta and Japan. 17) Among insecticides registered only for rice planthoppers, 51 active ingredients and 773 commercial products are available in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…A field WBPH resistance for chlorpyrifos was reported in Guizhou, Sichuan Province and many other rice growing areas of China in the past 15 years [ 11 , 12 , 13 ]. As a traditional and highly effective organophosphorus insecticide, Chlorpyrifos continues to be used in the control of pests such as Lepidoptera, Diptera, and Hemiptera [ 14 ]. However, due to the complex environment of pesticide use and the improvement of insect adaptability, organophosphate pesticides such as chlorpyrifos are suffering a new risk crisis of being banned.…”
Section: Introductionmentioning
confidence: 99%